Safe dental practice during the COVID-19 pandemic - Cheong, Joo Ming (IIUM Press, 2020)
Coronavirus disease 2019 (COVID-19) has caused widespread public health concerns and many disruptions in our daily life. Dental professionals may encounter patients with COVID-19 infections in their practice. This technical report provides suggestions and recommendations for implementing infection control in the dental office during COVID-19 pandemic.